"Crisis management in the hospitality sector SMEs in Pakistan during COVID-19″. (September 2021) - Burhan, Muhammad; Salam, Muhammad Talha; Hamdan, Omar Abou; Tariq, Hussain
Abstract: The COVID-19 pandemic has delivered one of the worst economic shocks in modern history and the hospitality sector has been severely affected. Since small businesses from the hospitality sector are known to be relatively more susceptible to the economic complications arising from a crisis, we explore the underlying factors and management practices that influence their continuity of operations as they continue to struggle with the on-going COVID-19 crisis in Pakistan. Using a phenomenological approach, in-depth interviews were conducted to comprehend the experiences of owners-managers. The findings show that government support, cordial relationships with stakeholders, self-determination of entrepreneurs and formal planning are the most crucial factors that shaped the immediate adjustments of operational activities in response to COVID-19. These resilient practices are hygiene concerns, increased promotion through social media, innovative marketing practices (e.g., revised offerings), operational cost-cutting and employee training to comply with changing standard operating procedures from the government and industry. The practical and theoretical implications are also discussed. Highlights: The impact of COVID-19 pandemic is relatively more detrimental to the global hospitality sector including Pakistan. It is vital to learn and disseminate the factors/practices that are shaping business continuity in restaurants amid fears of further waves of COVID-19. We explore the underlying factors and management practices that influence the continuity of operations in small restaurants in Pakistan amid COVID-19 crisis. Government support, cordial relationships with stakeholders, self-determination of entrepreneurs and formal planning shaped the immediate response to COVID-19. The resilient practices include hygienic operations, increased promotion through social media, innovative marketing practices and employee trainings.